2011
DOI: 10.1016/j.molcel.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and Transcriptome-wide Identification of RNA Binding Protein Target Sites

Abstract: Animal mRNAs are regulated by hundreds of RNA binding proteins (RBPs). The identification of RBP targets is crucial for understanding their function. A recent method, PAR-CLIP, uses photoreactive nucleosides to crosslink RBPs to target RNAs in cells prior to immunoprecipitation. Here, we establish iPAR-CLIP (in vivo PAR-CLIP) to determine, at nucleotide resolution, transcriptome-wide binding sites of GLD-1, a conserved, germline-specific translational repressor in C. elegans. We identified 439 reproducible tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
193
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(199 citation statements)
references
References 34 publications
6
193
0
Order By: Relevance
“…This includes miRISC components (48,52,53) , the Pumilio and FBF [Fem-3 binding factor] (PUF) domain family member Pumilio-2 (PUM2), the insulin-like growth factor 2 mRBPs 1, 2, and 3 (IGF2BP1-3), Quaking (QKI) (48) , heterogeneous nuclear ribonucleoprotein (hnRNP) particles (47) , T-cell intracellular antigen 1 (TIA1) and the related TIA1-like 1 (TIAL1) protein (54) , the splicing regulators TAR DNA binding protein 43 (TDP-43) (55) , Nova-1 and Nova-2 (43,56) , fragile X mental retardation protein (FMRP) (57) , the FET family proteins fused in sarcoma (FUS), Ewing sarcoma breakpoint region 1 (EWSR1) and TATA box binding protein (TBP)-associated factor 15 (TAF15) (58) , and human antigen R (HuR) (59,60) . Furthermore, PAR-CLIP has been applied in worms (61) and yeast (62) . Of note, databases for the deposition and visualization of CLIP experiments, such as CLIPZ (63) and PARalyzer (64) , have been set-up and are available to the community for data deposition or exploration (65) .…”
Section: Ribonomics -Global Methods For the Identifi Cation Of Rna-prmentioning
confidence: 99%
“…This includes miRISC components (48,52,53) , the Pumilio and FBF [Fem-3 binding factor] (PUF) domain family member Pumilio-2 (PUM2), the insulin-like growth factor 2 mRBPs 1, 2, and 3 (IGF2BP1-3), Quaking (QKI) (48) , heterogeneous nuclear ribonucleoprotein (hnRNP) particles (47) , T-cell intracellular antigen 1 (TIA1) and the related TIA1-like 1 (TIAL1) protein (54) , the splicing regulators TAR DNA binding protein 43 (TDP-43) (55) , Nova-1 and Nova-2 (43,56) , fragile X mental retardation protein (FMRP) (57) , the FET family proteins fused in sarcoma (FUS), Ewing sarcoma breakpoint region 1 (EWSR1) and TATA box binding protein (TBP)-associated factor 15 (TAF15) (58) , and human antigen R (HuR) (59,60) . Furthermore, PAR-CLIP has been applied in worms (61) and yeast (62) . Of note, databases for the deposition and visualization of CLIP experiments, such as CLIPZ (63) and PARalyzer (64) , have been set-up and are available to the community for data deposition or exploration (65) .…”
Section: Ribonomics -Global Methods For the Identifi Cation Of Rna-prmentioning
confidence: 99%
“…While a single RRE was sufficient for GLD-1-dependent regulation, multiple RREs within the 39 UTR increased the effect. Using PAR-CLIP (photoactivatable ribonucleoside-enhanced cross-linking and immunoprecipitation) in human embryonic kidney cells (HEK293) and C. elegans, our group and others expanded the QKI and GLD-1 target list and found similar RREs (Hafner et al 2010;Jungkamp et al 2011). In HEK293 cells, we found that >90% of the 2500 crosslinked binding sites present in 1500 transcripts contained at least one 5-nt YUAAY RRE.…”
mentioning
confidence: 93%
“…(E) EFL-1 targets (Gerstein et al 2010). (F) GLD-1 targets (Jungkamp et al 2011). n.s., not significant; **FDR , 1E-6; ***FDR , 1E-9.…”
Section: Sperm-only Adults Differ In Reprogramming Competencementioning
confidence: 99%